Exploring the smallest terrestrial planet: Dawn at Vesta - Raymond, Carol A.; Russell, C.T.; Jaumann, R.; McSween, H.Y.; Konopliv, A.S.; Asmar, S.; Coradini, A.S.; Desanctis, M.C.; Nathues, A.; Prettyman, T.H. (2011)
Dawn maps the surface of Vesta and Ceres and probes their internal density distributions, during one year of orbital operations at each body. Dawn carries a framing camera, a visible and infrared spectrometer (VIR), a gamma ray and neutron spectrometer (GRaND), and determines their gravity fields. The camera maps the surface in color, and obtains stereo data to derive global topography models. VIR determines the mineral composition of the surface and GRaND determines the elemental composition. Dawn maps from three science orbits at altitudes of ~2700 km, ~700 km, and ~200 km. Thus far, we have surveyed for moons around Vesta, accurately determined Vesta’s mass, refined the rotation axis, and have preliminary information on surface features and composition. The existence of abundant meteorites on Earth that came from Vesta or Vesta-derived material provides deep insight into geochemistry of Vesta, albeit without geologic context. We expect our Vesta data to provide that missing geologic context for the Howardite, Eucrite and Diogenite (HED) meteorites. According to the ages of the HED meteorites, Vesta formed in the solar system’s first few million years. Vesta likely accreted close to the time of a supernova explosion that provided short-half-life radionuclides supplying sufficient heat to melt Vesta, drive off the water and allow differentiation and formation of an iron core. Vesta is the second most massive asteroid in the main belt. It is thought to have a large impact structure surrounding its south pole. Initial observations with Dawn are not inconsistent with this hypothesis, but the terrain is unlike other impact basins. Outside this structure, the surface is heavily cratered. Vesta’s albedo is higher than most other asteroids, the Moon and Mercury. Vesta’s compositional diversity is more similar to the Moon and Mercury than other asteroids and it possesses a global 1-micron spectral feature due to ferrous iron absorption, which appears only locally on other airless bodies, and in stark contrast to ...